Effect of Concurrent Training Order With Electromyostimulation on Physical Performance in Young Elderly Women - Rouhollah Ranjbar; Mohsen Ghanbarzadeh; Masoud Nikbakht; Mehri Derakhshan Nejad (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: Aging is one of the stages of life that needs special attention due to the special conditions of this period of life. Inactivity and myasthenia due to aging are important factors in reducing the physical and functional activities in the elderly, which can affect their quality of life. On the other hand, electromyostimulation (EMS) is one of the modern training methods that can be suitable for disabilities in the elderly. Also, the training sequence in concurrent training is one of the variables of training that can affect its adaptations. This study aimed to compare the effect of exercise sequence in concurrent training with EMS on the motor performance of elderly women. Materials & Methods: In this semi-experimental single-blinded study, 50 healthy elderly female volunteers, age range of 60-70 years, were selected by random sampling divided randomly into the following groups (each group of 10 people): Aerobic-resistance training with EMS, resistance-aerobic exercise with EMS, rotational exercise (change of priority periodically in training sessions) with EMS, and rotational and control (without training) groups. The training protocol consisted of twelve weeks of exercise, three sessions per week, and each session three stages of warm-up (10-15 minutes), main exercises (20 minutes) and cooling (10 minutes). The main training program consisted of 20 minutes of parallel combination exercises, which were two 10-minute steps with a 3-5 minute intervals. Aerobic exercises were performed with the intensity of 70%-50% of maximum oxygen consumption and resistance exercises using body weight and elastic bands for different muscle groups. The training schedule was the same for all groups in terms of volume and intensity, with the only difference being in the exercise sequence and EMS presentation. Strength of the upper and lower torso muscles were measured with chest press and seated leg extension, respectively, maximum oxygen consumption (VO2 max) with a one-mile Rockport walking test, muscular endurance with a 2-minute marching on a spot-test and lower torso strength with a walking test on the slope in two stages before and after the intervention. Statistical analysis was performed using dependent t-tests and Covariance Analysis (ANCOVA) and Bonferroni post hoc test using SPSS software V. 22 and P≥0.05 was considered statistically significant. Results: Significant increase was observed in all measured dependent variables relative to the baseline values (P<0.001). In the study of intergroup changes, a significant increase was observed in VO2 max level, upper and lower torso strength, and muscular endurance in all of the intervention groups compared to the control group (P<0.001), but lower torso strength was significant only in the intervention groups with EMS compared to the control group (P<0.001). VO2 max changes and the lower torso strength in training groups with EMS were significantly higher than the groups without EMS (P<0.01). Also, the upper torso strength and the endurance of the lower torso muscles in the group with the priority of resistance training with EMS were higher than the combination group without EMS (P<0.01). Conclusion: Based on the results, it can be said that combined concurrent exercises are a useful method in promoting physical fitness and physical performance of elderly women, and the use of EMS can increase the effectiveness of adaptations resulting from exercise, especially lower torso strength in the elderly and can prevent complications associated with myasthenia. On the other hand, the training sequence with the priority of resistance training can be effective in increasing the effect of exercise on the variables of upper torso muscle strength and muscular endurance, but it does not have a significant effect on lower torso strength, cardiorespiratory endurance and lower torso strength.